GAMBARAN PERILAKU MASYARAKAT TERHADAP RISIKO PENYAKIT PES PADA DUSUN FOKUS DAN DUSUN TERANCAM PES - Cika Nirbaya Br Lubis; Agus Suwandono; Mateus Sakundarno (Jurnal Kesehatan Masyarakat (Undip), 2016)
Plague is a zoonotic disease caused by Yersinia pestis from rat flea bites. According to the results of trapping mice were successfully carried out in the region hamlet threatened Tlogosari and hamlets focus Taman year 2014-2015 has increased. Increasing the density of the rat is influenced by the behavior of people who are less clean and the lack of public knowledge about the plague and rats. The purpose of this study was to describe the density of rodents and social behavior at the focus hamlet and threatened hamlet. This study was a descriptive study by using quantitative methods and cross sectional study design. The population was rat gots caught up in the hamlet of focus and hamlets threatened and existing community mousetrap in his home in the hamlet of focus and Tlogosari threatened hamlets. The sample that was whole rat gets caught using live traps and all households mousetrap in that home at the hamlet of focus Taman and  Tlogosari  threatened hamlet with an age range 15-64 years. The results of this study showed that rats found in the hamlet focus was Rattus tanezumi while hamlet threatened were Rattus tanezumi and Rattus tiomaticus. The highest density of rats was at the hamlet threatened (6.8%). Flea infestations were found in the focus hamlet and threatened hamlet were X.cheopis and St.cognatus. Society in hamlets focus had less good behavior among other behaviors seed storage and trash management. While hamlet threatened, people who had less good behavior was the behavior of the use of  personal protective equipment and trash management behavior.